Design and Implementation FTTH GPON Network Design Based on Attenuation Measurement and Optisystem Modeling - Aprinal Adila Asril; Popy Maria; Ummul Khair; Silfia Rifka; Sri Nita (Yayasan Cita Cendekiawan Al Khwarizmi, 2026)
This study aims to design and implement a Fiber to the Home (FTTH) network based on Gigabit Passive Optical Network (GPON) technology using attenuation measurement as an approach to detect physical disturbances in optical fiber through modeling with Optisystem software. The research activities were conducted in a laboratory through several stages, including network topology design, system simulation using Optisystem, implementation of an FTTH trainer module, and attenuation measurement using an Optical Power Meter (OPM). Testing was carried out under various cable conditions, namely normal conditions, bending, damaged core, and variations in dropcore cable length to analyze their effects on attenuation values. The results showed that the attenuation values under normal conditions ranged from 14.94 to 16.23 dB, while under physical disturbance conditions such as bending and core damage, there was a significant increase in attenuation. The addition of cable length also contributed to an increase in attenuation of approximately 0.9 dB for every 5 meters. The Optisystem simulation results were consistent with the link power budget calculations and actual measurements, with a difference of approximately 0.1 dB. Furthermore, cable conditions with severe damage such as a broken core showed attenuation values exceeding 50 dB, which can be used as an indicator of physical disturbances. Overall, this study successfully demonstrates that the attenuation measurement method combined with Optisystem modeling is effective in detecting physical disturbances in FTTH GPON networks. The developed trainer module can also be used as a learning medium to understand attenuation characteristics and the performance of optical fiber networks in a laboratory environment.